Why we need Non absolute integral in place of Lebesgue integral? - Hemanta Kalita; Bipan Hazarika (Dera Natung Government College Research Journal)
In this survey note we discuss about non absolute integrable functions and we put our view about the question: Why we need Non absolute integral in place of Lebesgue integral? Various areas are discussed, where we can find Henstock-Kurzweil integral in place of Lebesgue integral.